Prospective Randomized Trial of Maintenance Immunosuppression With Rapid Discontinuation of Prednisone in Adult Kidney Transplantation. Issue 4 (22nd February 2013) - Suszynski, T. M.; Gillingham, K. J.; Rizzari, M. D.; Dunn, T. B.; Payne, W. D.; Chinnakotla, S.; Finger, E. B.; Sutherland, D. E. R.; Najarian, J. S.; Pruett, T. L.; Matas, A. J.; Kandaswamy, R.
Abstract : Rapid discontinuation of prednisone (RDP) has minimized steroid‐related complications following kidney transplant (KT). This trial compares long‐term (10‐year) outcomes with three different maintenance immunosuppressive protocols following RDP in adult KT. Recipients (n = 440; 73% living donor) from March 2001 to April 2006 were randomized into one of three arms: cyclosporine (CSA) and mycophenolate mofetil (MMF) (CSA/MMF,  n = 151); high‐level tacrolimus (TAC, 8–12 μg/L) and low‐level sirolimus (SIR, 3–7 μg/L) (TAC H /SIR L, n = 149) or low‐level TAC (3–7 μg/L) and high‐level SIR (8–12 μg/L) (TAC L /SIR H, n = 140). Median follow‐up was ∼7 years. There were no differences between arms in 10‐year actuarial patient, graft and death‐censored graft survival or in allograft function. There were no differences in the 10‐year actuarial rates of biopsy‐proven acute rejection (30%, 26% and 20% in CSA/MMF, TAC H /SIR L and TAC L /SIR H ) and chronic rejection (38%, 35% and 31% in CSA/MMF, TAC H /SIR L and TAC L /SIR H ). Rates of new‐onset diabetes mellitus were higher with TAC H /SIR L (p = 0.04), and rates of anemia were higher with TAC H /SIR L and TAC L /SIR H (p = 0.04). No differences were found in the overall rates of 16 other post‐KT complications. These data indicate that RDP‐based protocol yield acceptable 10‐year outcomes, but side effects differ based on the maintenance regimen used and should be considered when optimizing immunosuppression following RDP. Abstract : A prospective randomized trial comparing three different maintenance immunosuppressive regimens following rapid discontinuation of prednisone reports no differences in recipient and graft survival outcomes or graft function up to 10 years after kidney transplant, but reports differences in rates of drug‐related complications such as new‐onset diabetes and anemia.